Dietary carbohydrate requirement of lemon fin barb hybrid (Barbonymus gonionotus Bleeker 1849 ♀ X Hypsibarbus wetmorei Smith 1931 ♂) fingerlings - Aliyu, Sulaiman Muhammad (2017)
Carbohydrates are the widely available and cheap source of dietary energy. The optimal inclusion of carbohydrate in a fish diet can help in reducing the cost of feed and farm operation. The present study was conducted to determine the dietary carbohydrate requirement of lemon fin barb hybrid including the optimal inclusion, the best carbohydrate source and the optimal starch-fiber ratio. Three separate feeding trials were conducted in 100 l glass aquaria in which fish were fed at 4-6% body weight twice a day for 60 days. All treatments were triplicated. Growth, survival, hepatosomatic index, viserosomatic index, body composition and nutrient retention of the fish were estimated.